Exercise-induced euphoria and anxiolysis do not depend on endogenous opioids in humans. (April 2021) - Siebers, Michael; Biedermann, Sarah V.; Bindila, Laura; Lutz, Beat; Fuss, Johannes
Abstract: A runner's high describes a sense of well-being during endurance exercise characterized by euphoria and anxiolysis. It has been a widespread belief that the release of endogenous opioids, such as endorphins, underlie a runner's high. However, exercise leads to the release of two classes of rewarding molecules, endocannabinoids (eCBs) and opioids. In mice, we have shown that core features of a runner's high depend on cannabinoid receptors but not opioid receptors. In the present study, we aimed to corroborate in humans that endorphins do not play a significant role in the underlying mechanism of a runner's high. Thus, we investigated whether the development of two core features of a runner's high, euphoria and reduced anxiety levels, depend on opioid signaling by using the opioid receptor antagonist naltrexone (NAL) in a double-blind, randomized, placebo (PLA)-controlled experiment. Participants (N = 63) exhibited increased euphoria and decreased anxiety after 45 min of running (RUN) on a treadmill in a moderate-intensity range compared to walking (WALK). RUN led to higher plasma levels of the eCBs anandamide (AEA) and 2-arachidonoglycerol (2-AG). Opioid blockade did not prevent the development of euphoria and reduced anxiety as well as elevation of eCB levels following exercise. Moreover, the fraction of participants reporting a subjective runner's high was comparable in the NAL and PLA-treated group. Therefore, this study indicates that the development of a runner's high does not depend on opioid signaling in humans, but makes eCBs strong candidates in humans, as previously shown in mice. Highlights: Exercise-induced euphoria and anxiolysis are independent of direct occupancy of endogenous μ-opioid receptors binding. Running reduces anxiety levels in a human elevated plus-maze. Running stimulates the endocannabinoid system. Endocannabinoids are better candidates than endorphins to explain a runner's high in humans.